High-strength pervious concrete and preparation method thereof

By using fiber embedded composite porous ceramics in permeable concrete, a three-dimensional network structure of burr-like ceramics is formed, which solves the problem that it is difficult to simultaneously improve the mechanical properties and permeability of concrete in the prior art, and achieves high-strength, high-permeability concrete preparation.

CN119874262APending Publication Date: 2025-04-25SUZHOU SHANGJIAN HANGXIN CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411565766.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to improve the mechanical properties and water permeability of water permeability at the same time. The two are usually contradictory, and it is difficult to prepare high-strength, high-permeability concrete.

Method used

By adding fiber embedded composite porous ceramics to the concrete, instead of traditional fibers and porous ceramics, burr-like ceramics are prepared by specific preparation methods, thereby forming a three-dimensional network structure and improving the mechanical properties and water permeability of the concrete.

Benefits of technology

It has achieved the preparation of high-strength permeable concrete, with excellent mechanical properties and permeable properties, and is suitable for concrete pavement and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides high-strength pervious concrete which comprises the following components: 300-400 parts of cement, 500-700 parts of fine aggregate, 700-900 parts of fiber embedded type composite porous ceramsite, 10-20 parts of fly ash, 10-20 parts of slag, 10-20 parts of silica fume and 150-180 parts of water, in the fiber embedded type composite porous ceramsite, 400-500 parts of ceramsite with the particle size range of 5-8 mm, 10-20 parts of slag with the particle size range of 5-8 mm, 10-20 parts of silica fume with the particle size range of 5-8 mm, 10-20 parts of silica fume with the particle size range of 5-8 mm and 10-20 parts of water with the particle size range of 5-8 mm. And 300-400 parts of ceramsite with the particle size range of 8-15 mm. According to the invention, the fiber embedded composite porous ceramsite is added into the concrete to replace previous fibers and porous ceramsite, so that the pervious concrete has water permeability and can ensure mechanical properties at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete, and in particular to high-strength permeable concrete and a preparation method thereof. Background Art

[0002] Pervious concrete is an eco-friendly concrete with continuous voids, produced through a specialized process using a specific mix ratio of cement, water, aggregate, admixtures, additives, and inorganic pigments. Its apparent density typically ranges from 1600 to 2100 kg / m3, its 28-day compressive strength from 10 to 30 MPa, its flexural strength from 2 to 6 MPa, and its permeability from 0.5 to 20 mm / s. Compared to conventional concrete, pervious concrete offers numerous advantages, including water permeability, air permeability, water purification, sound absorption and noise reduction, groundwater conservation, mitigation of the urban heat island effect, and soil ecological improvement. Consequently, guided by the principles of sustainable development and ecological balance, developed countries such as Japan, South Korea, Europe, and the United States began researching and developing pervious concrete over 50 years ago. National standards and specifications have been established for its mix design, construction, maintenance, and management. It has been widely applied in various fields, including municipal engineering, landscape engineering, environmental engineering, and ecological and environmental protection projects, achieving excellent results. Pervious concrete consists of a skeleton structure and pores. The density of the skeleton structure can be increased by increasing the paste-aggregate ratio, and reducing porosity improves the mechanical properties of pervious concrete. However, the permeability coefficient is positively correlated with porosity, so decreasing porosity leads to decreased permeability. Generally speaking, porosity affects both the mechanical and permeability properties of pervious concrete, and these two factors conflict with each other, making it difficult to produce high-strength, highly permeable concrete. Summary of the Invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a high-strength permeable concrete, by adding fiber-embedded composite porous ceramsite to the concrete to replace the previous fibers and porous ceramsite, so that the permeable concrete has water permeability while ensuring mechanical properties.

[0004] Technical solution: A high-strength permeable concrete, comprising the following components: 300-400 parts of cement 500-700 parts of fine aggregate Fiber embedded composite porous ceramsite 700-900 parts 10-20 parts fly ash 10-20 parts slag 10-20 parts silica fume 150-180 parts water Among them, the fiber-embedded composite porous ceramsite contains 400-500 parts of ceramsite with a particle size range of 5-8 mm, and 300-400 parts of ceramsite with a particle size range of 8-15 mm. Preferably, the preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash was added to obtain a fly ash solution; S14. The ceramsite is added to the fly ash solution, and then the ceramsite is removed and added to the mixture of the alumina fiber membrane precursor and the alumina fiber precursor, and stirred thoroughly so that the alumina fiber membrane precursor and the alumina fiber precursor adhere to the surface of the ceramsite; S15. Repeat the above steps 1-3 times to obtain burr-shaped ceramsite; S16. Drying and sintering the burr-shaped ceramsite to obtain fiber-embedded composite porous ceramsite. Preferably, the method for preparing the alumina fiber membrane precursor comprises the following steps: S1-1. Add aluminum nitrate to water, mix and stir to dissolve, then add nitric acid and glacial acetic acid, stir and mix evenly, add aluminum isopropoxide, and stir to obtain a transparent solution, the molar ratio of aluminum nitrate and aluminum isopropoxide is 1:0.6-1.5, the volume ratio of water, nitric acid and glacial acetic acid is 1:0.3-0.4:0.2-0.3, then add PVP, the amount of PVP added is 1.4-1.8wt%, to obtain a spinnable sol; S1-2. Electrospin the spinnable sol and crush it to obtain an alumina fiber membrane precursor. Preferably, the method for preparing the alumina fiber precursor comprises the following steps: S2-1. Add aluminum nitrate to water, mix and stir to dissolve, then add nitric acid and glacial acetic acid, stir and mix evenly, add aluminum isopropoxide, and stir to obtain a transparent solution, the molar ratio of aluminum nitrate and aluminum isopropoxide is 1:0.6-1.5, the volume ratio of water, nitric acid and glacial acetic acid is 1:0.3-0.4:0.2-0.3, and then add PVP, the amount of PVP added is 5-8wt%, to obtain a spinnable sol; S1-2. The spinnable sol is wet-spun, the coagulation bath is water, the spinneret diameter is 1-1.2mm, and crushed to obtain an alumina fiber precursor. Preferably, in step S13, the mass ratio of hydroxypropyl methylcellulose, fly ash and water is 2-4:2-4:100. Preferably, in step S14, the area of ​​the alumina fiber membrane precursor is 2-4 cm2, and the length of the alumina fiber precursor is 2-3 cm. Preferably, the drying temperature in step S16 is 130-150°C, the drying time is 2-5 hours, and the sintering temperature is raised to 600°C at a rate of 1-2°C / min, kept at this temperature for 2 hours, and then raised to 1050-1100°C at a rate of 3-5°C / min, and kept at this temperature for 30-60 minutes. The above-mentioned method for preparing high-strength permeable concrete includes the following steps: first, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 5-10 minutes, then adding 60-70% of the formula amount of water, stirring evenly, and then adding the remaining water, stirring for 1-3 minutes, and discharging to obtain high-strength permeable concrete slurry. Beneficial effects: The high-strength permeable concrete of the present invention has the following advantages: 1. The high-strength permeable concrete of the present invention changes the form of conventional ceramsite and reinforcing fibers. In the past, the mechanical properties of permeable concrete were improved by adding ceramic fibers, steel fibers, carbon fibers, etc. In the present invention, porous ceramsite containing fibers is directly prepared. Ceramsite is not a smooth structure as in the past. One-dimensional and two-dimensional fibers or fiber membranes are prepared by different spinning methods and combined with ceramsite during granulation. The combination of fibers and fiber membranes with ceramsite is similar to the preparation method of "rolling glutinous rice balls". Finally, burr-shaped ceramsite is obtained by sintering. When filled into concrete, a three-dimensional network structure is obtained. During the molding process, adjacent burr-shaped ceramsites are in close contact with each other and connected front to back. After consolidation and molding, a number of interconnected porous channels are formed at the locations where most of the burr-shaped ceramsites exist, so that the prepared material has the high strength and permeability required for concrete pavement. 2. In the present invention, the unsintered alumina precursor is directly mixed with the unsintered ceramsite. After the two are mixed to a specified size, they are sintered together to improve the bonding strength between the fiber and the fiber membrane and the ceramsite. 3. In the present invention, two fiber-embedded composite porous ceramsite with different particle sizes are added to the concrete. The addition of coarse and fine aggregates with different particle sizes can increase more contact sites in the concrete and improve the mechanical properties of the concrete. DETAILED DESCRIPTION The present invention will be further described below in conjunction with examples, which are provided to explain the present invention and are not limited to the following examples: Example 1 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 5 minutes, then adding 60% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 300 parts, fine aggregate is 500 parts, fiber-embedded composite porous ceramsite is 700 parts, fly ash is 10 parts, slag is 10 parts, silica fume is 10 parts, and water is 150 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 400 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 2:4:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:1, where the area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps twice to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite was dried and sintered at a drying temperature of 130 ° C for 5 h. The sintering temperature was raised to 600 ° C at a rate of 2 ° C / min, held for 2 h, and then raised to 1100 ° C at a rate of 5 ° C / min and held for 30 min to obtain a fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.6, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.3:0.2. PVP was then added, and PVP was added in an amount of 1.4wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.6, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.4:0.2. PVP was then added, and PVP was added in an amount of 5wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1 mm, and then pulverized to obtain an alumina fiber precursor. Example 2 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 10 minutes, then adding 70% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 1 minute, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 400 parts, fine aggregate is 700 parts, fiber-embedded composite porous ceramsite is 900 parts, fly ash is 20 parts, slag is 20 parts, silica fume is 20 parts, and water is 180 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 500 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 4:2:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:2, where the area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps 3 times to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite was dried and sintered at a drying temperature of 150 ° C for 2 h. The sintering temperature was raised to 600 ° C at a rate of 1 ° C / min, held for 2 h, and then raised to 1050 ° C at a rate of 3 ° C / min and held for 60 min to obtain a fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.7, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.4:0.3. PVP was then added, and PVP was added in an amount of 1.8wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.7, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.4:0.3. PVP was then added, and PVP was added in an amount of 8wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1.2 mm, and then pulverized to obtain an alumina fiber precursor. Example 3 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 6 minutes, then adding 60% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 2 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 330 parts, fine aggregate is 650 parts, fiber-embedded composite porous ceramsite is 750 parts, fly ash is 12 parts, slag is 18 parts, silica fume is 18 parts, and water is 160 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, respectively. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 2.5:3.5:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:1.5, where the area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps twice to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite is dried and sintered at a drying temperature of 135°C for 4 hours. The sintering temperature is increased to 600°C at a rate of 1°C / min, kept at this temperature for 2 hours, and then increased to 1050°C at a rate of 4°C / min and kept at this temperature for 40 minutes to obtain fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.8, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.3:0.2. PVP was then added, and PVP was added in an amount of 1.5wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.85, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.2. PVP was then added, and PVP was added in an amount of 8wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1 mm, and then pulverized to obtain an alumina fiber precursor. Example 4 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 9 minutes, then adding 70% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 380 parts, fine aggregate is 550 parts, fiber-embedded composite porous ceramsite is 850 parts, fly ash is 18 parts, slag is 18 parts, silica fume is 12 parts, and water is 170 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 450 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 3.5:2.5:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:2, where the area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps 3 times to obtain burr-shaped ceramsite; S16. Dry and sinter the burr-shaped expanded clay at a drying temperature of 145°C for 3 hours. The sintering temperature is increased at a rate of 2°C / min to 600°C, kept at this temperature for 2 hours, and then increased at a rate of 5°C / min to 1100°C and kept at this temperature for 50 minutes to obtain fiber-embedded composite porous expanded clay. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.9, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.4:0.25. PVP was then added, and PVP was added in an amount of 1.7wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.9, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.3:0.3. PVP was then added, and PVP was added in an amount of 5wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1.2 mm, and then pulverized to obtain an alumina fiber precursor. Example 5 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 8 minutes, then adding 65% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 350 parts, fine aggregate is 600 parts, fiber-embedded composite porous ceramsite is 850 parts, fly ash is 15 parts, slag is 15 parts, silica fume is 15 parts, and water is 165 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 500 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 3:3:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:3, where the area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps once to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite is dried and sintered at a drying temperature of 140°C for 3 hours. The sintering temperature is increased at a rate of 2°C / min to 600°C, kept at this temperature for 2 hours, and then increased at a rate of 4°C / min to 1100°C and kept at this temperature for 45 minutes to obtain fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.75, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 1.6wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.85, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 7wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1.1 mm, and then pulverized to obtain an alumina fiber precursor. Comparative Example 1 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 8 minutes, then adding 65% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 350 parts, fine aggregate is 600 parts, fiber embedded composite porous ceramsite with a particle size range of 5-8mm is 850 parts, fly ash is 15 parts, slag is 15 parts, silica fume is 15 parts, and water is 165 parts; The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 3:3:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane precursor and alumina fiber precursor with a mass ratio of 1:1, where the area of ​​the alumina fiber membrane precursor is 2-4 cm2 , the length of the alumina fiber precursor is 2-3 cm, and the alumina fiber membrane precursor and the alumina fiber precursor are fully stirred to adhere to the surface of the ceramsite; S15. Repeat the above steps twice to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite is dried and sintered at a drying temperature of 140°C for 3 hours. The sintering temperature is increased at a rate of 2°C / min to 600°C, kept at this temperature for 2 hours, and then increased at a rate of 4°C / min to 1050°C and kept at this temperature for 45 minutes to obtain fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.75, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 1.6wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun and crushed to obtain an alumina fiber membrane precursor; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.85, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 7wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1.1 mm, and then pulverized to obtain an alumina fiber precursor. Comparative Example 2 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, porous ceramsite, alumina fiber, fly ash, slag, and silica fume for 8 minutes, then adding 65% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 350 parts, fine aggregate is 600 parts, porous ceramsite with a particle size of 5-15mm is 600 parts, alumina fiber with a length of 1-3cm, fly ash is 15 parts, slag is 15 parts, silica fume is 15 parts, and water is 165 parts. Comparative Example 3 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 8 minutes, then adding 65% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 350 parts, fine aggregate is 600 parts, fiber-embedded composite porous ceramsite is 850 parts, fly ash is 15 parts, slag is 15 parts, silica fume is 15 parts, and water is 165 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 500 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 3:3:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to a mixture of alumina fiber membrane and alumina fiber with a mass ratio of 1:1, where the area of ​​the alumina fiber membrane is 2-4 cm 2 The length of the alumina fiber is 2-3 cm, and the alumina fiber film and alumina fiber are adhered to the surface of the ceramsite by stirring thoroughly; S15. Repeat the above steps twice to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite is dried and sintered at a drying temperature of 140°C for 3 hours. The sintering temperature is increased at a rate of 2°C / min to 600°C, kept at this temperature for 2 hours, and then increased at a rate of 4°C / min to 1100°C and kept at this temperature for 45 minutes to obtain fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.75, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 1.6wt% to obtain a spinnable sol. S1-2. The spinnable sol is electrospun, crushed to obtain an alumina fiber membrane precursor, and the precursor is sintered to obtain an alumina fiber membrane; The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1: 0.85, and the volume ratio of water, nitric acid and glacial acetic acid was 1: 0.35: 0.25. PVP was then added, and PVP was added in an amount of 7wt% to obtain a spinnable sol. S1-2. The spinnable sol is wet-spun with water as the coagulation bath and a spinneret diameter of 1.1 mm. The alumina fiber precursor is obtained by pulverizing the alumina fiber precursor, and the precursor is sintered to obtain alumina fibers. Comparative Example 4 A high-strength permeable concrete comprising the following components: The method for preparing high-strength permeable concrete comprises the following steps: firstly, mixing cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag, and silica fume for 8 minutes, then adding 65% of the formula amount of water, stirring evenly, then adding the remaining amount of water, stirring for 3 minutes, and discharging to obtain high-strength permeable concrete slurry; Among them, cement is 350 parts, fine aggregate is 600 parts, fiber-embedded composite porous ceramsite is 850 parts, fly ash is 15 parts, slag is 15 parts, silica fume is 15 parts, and water is 165 parts; among them, the fiber-embedded composite porous ceramsite has a particle size range of 5-8mm and a particle size range of 8-15mm, which is 500 parts. The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added and mixed, and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose was added to water and dissolved, and then fly ash, hydroxypropyl methylcellulose, fly ash and water were added in a mass ratio of 3:3:100 to obtain a fly ash solution; S14. Add ceramsite to the fly ash solution, then remove the ceramsite and add it to the alumina fiber membrane precursor. The area of ​​the alumina fiber membrane precursor is 2-4 cm 2 , stirring thoroughly to make the alumina fiber membrane precursor and the alumina fiber precursor adhere to the surface of the ceramsite; S15. Repeat the above steps 3 times to obtain burr-shaped ceramsite; S16. The burr-shaped ceramsite is dried and sintered at a drying temperature of 140°C for 3 hours. The sintering temperature is increased at a rate of 2°C / min to 600°C, kept at this temperature for 2 hours, and then increased at a rate of 4°C / min to 1100°C and kept at this temperature for 45 minutes to obtain fiber-embedded composite porous ceramsite. The preparation method of the alumina fiber membrane precursor comprises the following steps: S1-1. Aluminum nitrate was added to water, mixed and stirred to dissolve, and then nitric acid and glacial acetic acid were added. After stirring and mixing, aluminum isopropoxide was added and stirred to obtain a transparent solution. The molar ratio of aluminum nitrate and aluminum isopropoxide was 1:0.8, and the volume ratio of water, nitric acid and glacial acetic acid was 1:0.35:0.25. PVP was then added, and PVP was added in an amount of 2wt% to obtain a spinnable sol. S1-2. The spinnable sol is subjected to electrospinning and crushed to obtain an alumina fiber membrane precursor. Performance testing: The mechanical properties of permeable concrete were tested in accordance with GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"; the permeability coefficient was tested in accordance with GB / T 25993-2010 "Permeable Pavement Bricks and Permeable Road Slabs"; After measuring the dry density ρ 干 The true density ρ of the test block is determined according to GB / T 208-2014 "Determination of density of cement" 真 , then the porosity P is calculated as follows: P = (ρ 真 -ρ 干 ) / ρ 真 *100%. Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A high-strength permeable concrete, characterized in that: Includes the following ingredients: 300-400 parts of cement Fine aggregate 500-700 parts Fiber embedded composite porous ceramsite 700-900 copies Fly ash 10-20 parts 10-20 parts of slag Silica fume 10-20 parts 150-180 parts water Among them, the fiber-embedded composite porous ceramsite has 400-500 parts of ceramsite with a particle size range of 5-8 mm, and 300-400 parts of ceramsite with a particle size range of 8-15 mm.

2. The high-strength permeable concrete according to claim 1, characterized in that: The preparation method of the fiber-embedded composite porous ceramsite comprises the following steps: S11. After the fly ash and clay are dried and ground, water is added to mix and then the clay fly ash mixture is prepared; S12. The mixture is granulated into ceramsite having a particle size of 2-3 mm; S13. Hydroxypropyl methylcellulose is added to water to dissolve, and then fly ash is added to obtain a fly ash solution; S14. adding ceramsite to the fly ash solution, then taking out the ceramsite and adding it to the mixture of the alumina fiber membrane precursor and the alumina fiber precursor, stirring thoroughly so that the alumina fiber membrane precursor and the alumina fiber precursor adhere to the surface of the ceramsite; S15. Repeat the above steps 1-3 times to obtain burr-shaped ceramsite; S16. Drying and sintering the burr-shaped ceramsite to obtain fiber-embedded composite porous ceramsite.

3. The high-strength permeable concrete according to claim 2, characterized in that: The method for preparing the alumina fiber membrane precursor comprises the following steps: S1-1. Add aluminum nitrate into water, stir and dissolve, then add nitric acid and glacial acetic acid, stir and mix evenly, add aluminum isopropoxide, stir to obtain a transparent solution, the molar ratio of aluminum nitrate to aluminum isopropoxide is 1:0.6-1.5, the volume ratio of water, nitric acid and glacial acetic acid is 1:0.3-0.4:0.2-0.3, then add PVP, the amount of PVP added is 1.4-1.8wt%, to obtain a spinnable sol; S1-2. Electrospin the spinnable sol and pulverize it to obtain an alumina fiber membrane precursor.

4. The high-strength permeable concrete according to claim 3, characterized in that: The preparation method of the alumina fiber precursor comprises the following steps: S2-1. Add aluminum nitrate into water, stir and dissolve, then add nitric acid and glacial acetic acid, stir and mix evenly, add aluminum isopropoxide, stir to obtain a transparent solution, the molar ratio of aluminum nitrate to aluminum isopropoxide is 1:0.6-1.5, the volume ratio of water, nitric acid and glacial acetic acid is 1:0.3-0.4:0.2-0.3, then add PVP, the amount of PVP added is 5-8wt%, to obtain a spinnable sol; S1-2. Wet-spin the spinnable sol, the coagulation bath is water, the spinneret hole diameter is 1-1.2mm, and crush to obtain an alumina fiber precursor.

5. The high-strength permeable concrete according to claim 2, characterized in that: In the step S13, the mass ratio of hydroxypropyl methylcellulose, fly ash and water is 2-4:2-4:

100.

6. The high-strength permeable concrete according to claim 2, characterized in that: In the step S14, the area of ​​the alumina fiber membrane precursor is 2-4 cm2, and the length of the alumina fiber precursor is 2-3 cm.

7. The high-strength permeable concrete according to claim 2, characterized in that: In step S16, the drying temperature is 130-150°C, the drying time is 2-5h, the sintering temperature is increased to 600°C at a rate of 1-2°C / min, kept at that temperature for 2h, then increased to 1050-1100°C at a rate of 3-5°C / min, and kept at that temperature for 30-60min.

8. The method for preparing high-strength permeable concrete according to claim 1, characterized in that: The following steps are involved: First, cement, fine aggregate, fiber-embedded composite porous ceramsite, fly ash, slag and silica fume are mixed for 5-10 minutes, and then 60-70% of the formula amount of water is added, and after stirring evenly, the remaining water is added, and the material is stirred for 1-3 minutes to obtain high-strength permeable concrete slurry.